Perawatan Periodontal pada Pasien Lupus Eritematosus Sistemik - Nur Rahma Prihantini; Sri Lelyati C Masulili (Faculty of Dentistry, Universitas Gadjah Mada, 2012)
Background: Systematic disease is a risk factor in periodontal disease. In contrast, severe generalize periodontal disease may also contribute to the development of certain systemic diseases and has and adverse affect in controlling the systemic disease. The majority of systemic diseases manifest in the oral cavity, one of which is systemic Lupus Erythematosus (SLE)., anautoimmune chronic systemic diseases. To date, the etiology of Lupus Erythematosus is still not clear, but the prognosis can become good if the adequate theraphy is given. SLE have a fairly high incidence, but the dangers of this disease is still not widely understood by the public. Purpose: To demonstrate how to manage the oral manifestations of SLE, as it must be done carefully so that patients ca get appropriate treatment to be successful, and the patients with oral manifestations similar to SLE can have a more thorough axamination. Cases: Two patients with SLE and symptoms of easy bleeding gums, frequent stomatitis, dry mouth, and mobile teeth. In both cases, there is gingival hyperemia, edema, pockets of 3-6 mm (case 1) and 3-4 mm (case 2). Prior to dental treatment, both patients are consulted to an internist. Treatment: Periodontal initial treatment such as DHE, scaling, and tooth restorations. Gradual scaling done in multiple visits, followed by gingival curettage. Conclusion: A good periodontal treatment can reduce gingival inflammation, and relatively improve oral hygiene, so it can be expected to increase body immunity.